2024
DOI: 10.1186/s40164-023-00470-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of biliary tract cancers reveals distinct genomic landscapes between circulating and tissue tumor DNA

Clémence Astier,
Carine Ngo,
Léo Colmet-Daage
et al.

Abstract: Biliary tract cancers (BTCs) are heterogeneous malignancies with dismal prognosis due to tumor aggressiveness and poor response to limited current therapeutic options. Tumor exome profiling has allowed to successfully establish targeted therapeutic strategies in the clinical management of cholangiocarcinoma (CCA). Still, whether liquid biopsy profiling could inform on BTC biology and patient management is unknown. In order to test this and generate novel insight into BTC biology, we analyzed the molecular land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Moreover, Okamura et al indicated a higher concordance when comparing matching ctDNA-metastatic tumor tissues with ctDNA-primary tumor tissues [145]. Blood-based liquid biopsy can also be used to identify clinically relevant genomic alterations when guiding precision medicine [144,[146][147][148]. A retrospective analysis of the ClarIDHy trial, which examined the efficacy of the IDH1 inhibitor ivosidenib in mutant IDH1 cholangiocarcinoma, showed that the clearance of IDH1 mutation, as assessed in plasma ctDNA in patients monitored over time, was associated with disease control [149].…”
Section: Liquid Biopsy Based On Blood Samplesmentioning
confidence: 99%
“…Moreover, Okamura et al indicated a higher concordance when comparing matching ctDNA-metastatic tumor tissues with ctDNA-primary tumor tissues [145]. Blood-based liquid biopsy can also be used to identify clinically relevant genomic alterations when guiding precision medicine [144,[146][147][148]. A retrospective analysis of the ClarIDHy trial, which examined the efficacy of the IDH1 inhibitor ivosidenib in mutant IDH1 cholangiocarcinoma, showed that the clearance of IDH1 mutation, as assessed in plasma ctDNA in patients monitored over time, was associated with disease control [149].…”
Section: Liquid Biopsy Based On Blood Samplesmentioning
confidence: 99%
“…The pathway to obtain high-quality, reliable NGS data is full of challenges, notably from the pre-analytical phase until the NGS sequencing itself. The pre-analytical phase is critical as it encompasses all steps from the initial sample collection to the preparation of nucleic acids for sequencing extracted from formalin-fixed paraffin-embedded (FFPE) ( Gu et al, 2023 ; Astier et al, 2024 ; Hatanaka et al, 2024 ).…”
Section: Next-generation Sequencing: a New Standard In Cancer Managementmentioning
confidence: 99%